Reliability of Panoramic-Radiograph to Determine the Position of Third-Molar from Inferior-Alveolar-Canal - Fauzi, A.A.; Parker, M.E.; Norval, E.; Nambiar, Phrabhakaran (Penerbit Universiti Kebangsaan Malaysia, 2017)
Cone-beam-computed-tomography (CBCT) has been useful in providing insights of relevant anatomy prior to surgical procedures, including the assessment of the proximity of impacted mandibular-third-molar to the inferior-alveolar-canal (IAC). It is important to understand the reliability of conventional panoramic-radiograph in the assessment of this criterion since it is more commonly used as first line radiographic approach due to its availability and lower radiation dose. This study aimed to investigate the reliability of conventional panoramic-radiograph in the evaluation of the proximity of impacted mandibular-third-molar root tip to the IAC by correlating the results with CBCT. A total of 65 root tips of impacted mandibular-third-molars that had both panoramic radiographs and CBCT images were included in this retrospective study. Two trained observers participated in all image evaluations. A prepared standard 1 cm ruler was used to measure the proximity of the third-molar root apices to the IACs. Measurements recorded in this study were categorized into positive (root apex above a roof of IAC), zero (root apex was superimposed on IAC) and negative (root apex below a roof of IAC). Data analysis was carried out using student t-test. In this study, both observers recorded statistically significant differences in the measurement between third-molars root apices and the IAC from panoramic radiographs and CBCT images. The low reliability of panoramic radiograph to assess the vertical proximity between these two anatomical structures suggests the importance of additional assessment with CBCT in cases where panoramic radiograph shows superimposition of the third molar root on the roof of the canal and presence of root below the roof of the IAC.